INFLUENCE OF JUDICIAL NORM-CONTROL ON ENSURING HUMAN RIGHTS - Toksanbaeva Ayjamal Mangytbay kizi (Galaxy International Interdisciplinary Research Journal, 2022)
Currently, one of the most important areas of the legal doctrine of most foreign countries is the creation of a fair and stable legislative system. The complexity and acuteness of this issue is manifested not only in identifying and introducing effective norms into the process of legal regulation of social relations, but also in understanding its methodological and conceptual foundations, correctly defining the essence and subjects of legal regulation. In this case, scientific research is being conducted to further improve the work of rule-making in developed countries, including ensuring the legality and promotion of legislation, conducting a comprehensive examination, including prevention of disputes over departmental regulations. The norm has a special place in the field of creativity of legislative acts. In particular, a separate approach is needed on the part of public administration bodies when issuing departmental legal documents. The control over these documents by the court will prevent human rights violations. This article describes this problem.